2021
DOI: 10.3791/62590-v
|View full text |Cite
|
Sign up to set email alerts
|

Application of <em>Lucilia sericata</em> Larvae in Debridement of Pressure Wounds in Outpatient Settings

Abstract: Biological therapy using Lucilia sericata larvae has numerous advocates worldwide, yet it is still fairly unknown and not commonly applied in daily practice because of the limited awareness and insufficient experience of medical and nursing personnel.There are case reports suggesting that maggot therapy can be applied and supported by lay caregivers, provided they are supervised and informed by physicians/nurses.The foregoing observation suggests that the method should be considered for implementation by a wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The application of MDT has proven effective in managing chronic wounds such as diabetic foot ulcers [ 35 ], venous leg ulcers [ 36 ] and pressure sores [ 37 ] as well as other kinds of wounds where traditional therapies often fail [ 11 ]. Furthermore, some studies have shown that wounds treated with MDT have lower rates of bacterial colonization, including by antibiotic-resistant strains, supporting MDT's potential role in the fight against AMR.…”
Section: Maggot Debridement Therapy: An Old Approach With New Potentialmentioning
confidence: 99%
See 2 more Smart Citations
“…The application of MDT has proven effective in managing chronic wounds such as diabetic foot ulcers [ 35 ], venous leg ulcers [ 36 ] and pressure sores [ 37 ] as well as other kinds of wounds where traditional therapies often fail [ 11 ]. Furthermore, some studies have shown that wounds treated with MDT have lower rates of bacterial colonization, including by antibiotic-resistant strains, supporting MDT's potential role in the fight against AMR.…”
Section: Maggot Debridement Therapy: An Old Approach With New Potentialmentioning
confidence: 99%
“…The utilization of maggots in medical treatment often elicits a natural repulsion or discomfort among many individuals. This psychological barrier may stem from cultural perceptions, personal phobias, or general unease with the unconventional nature of the therapy [ 11 , 37 ]. The challenge, then, lies not just in demonstrating the efficacy and safety of MDT but also in educating patients and healthcare providers to overcome these instinctive reactions.…”
Section: Maggot Debridement Therapy: An Old Approach With New Potentialmentioning
confidence: 99%
See 1 more Smart Citation